Impacto de los medios audiovisuales en la conducta social y comunicativa de los habitantes del Sector Lotización Lupita, Cantón Buena Fe - Alcivar Lucas, Maria Fernanda (2019)
The audiovisual media have undoubtedly changed the perspective of the human being in terms of information and entertainment, its facilities to access them, its multifunctional uses puts the performance of man in check and that if it is proposed with the accelerated pace of growth, it can replace it Easy in several of your tasks. In education, it has functioned as excellent academic strategies giving the facilities to the teacher as the student to be able to share first-hand information according to the new educational requirements aimed at the future and achievements of professional objectives. When it comes to content for the media, involving in this case the cinema and mass media television of greater coverage refers to a set of graphic elements, illustrations, photographs, spellings, cartoons, animations and auditory or sound devices, which It ensures they get the attention of the receiver, the same that makes use of their auditory and visual senses, in addition to causing a reaction in it, according to the message received. Currently the individual moves to the beat of technology, the media power that current technology has on the human being is surprising, every day younger, adults and children join their total dependence, smartphones have allowed to shorten the time and the distance in a matter of seconds, giving comforts and facilities that in previous years was a difficult dream to achieve. But these same comforts can turn against people, causing damage directly in their lives, such as emotional communication in their environment, damage to their physical and psychological health because the audiovisual media have the objective of working on emotions of the human being for a greater impact depending on what they see